Cold tolerance is unaffected by oxygen availability despite changes in anaerobic metabolism - Boardman, Leigh; Sørensen, Jesper G; Koštál, Vladimír; Šimek, Petr; Terblanche, John S (Scientific reports, 2016)
Insect cold tolerance depends on their ability to withstand or repair perturbations in cellular homeostasis caused by low temperature stress. Decreased oxygen availability (hypoxia) can interact with low temperature tolerance, often improving insect survival. One mechanism proposed for such responses is that whole-animal cold tolerance is set by a transition to anaerobic metabolism. Here, we provide a test of this hypothesis in an insect model system (Thaumatotibia leucotreta) by experimental manipulation of oxygen availability while measuring metabolic rate, critical thermal minimum (CTmin), supercooling point and changes in 43 metabolites in moth larvae at three key timepoints (before, during and after chill coma). Furthermore, we determined the critical oxygen partial pressure below which metabolic rate was suppressed (c. 4.5 kPa). Results showed that altering oxygen availability did not affect (non-lethal) CTmin nor (lethal) supercooling point. Metabolomic profiling revealed the upregulation of anaerobic metabolites and alterations in concentrations of citric acid cycle intermediates during and after chill coma exposure. Hypoxia exacerbated the anaerobic metabolite responses induced by low temperatures. These results suggest that cold tolerance of T. leucotreta larvae is not set by oxygen limitation, and that anaerobic metabolism in these larvae may contribute to their ability to survive in necrotic fruit.
Keywords: Animals; homeostáza; můry; Acclimatization; bazální metabolismus; Basal Metabolism; Homeostasis; Moths; aklimatizace; Metabolomics; Cold Temperature; Cold-Shock Response; metabolomika; Oxygen; reakce na chladový šok; Amino Acids; Anaerobiosis; Larva; zvířata; anaerobióza; nízká teplota; aminokyseliny; kyslík; larva